Socio economic aspect of organic farming practices for improving farmer’s income in some locations of Kerala, India (Bangladesh Journal of Agricultural Research, 2019)
Agriculture is the major source of livelihood and is under the big threat of liberalization and modernization. Organic farming is eco-friendly, promotes sustainable development, protects the fertility of the soil and ensures long term crop income to the farmer. In 2018, total area under organic certification process is 3.56 million hectare and produced around 1.70 million MT of certified organic products. In Kerala, the total area under organic farming stands at 15790.49 hectare. Organic farmers fail to capture the market for selling their products and have less capacity in the competing world, leads to worse financial situation of farmers. The total volume of export during 2017-18 was 4.58 lakh MT. Fair trade has flourished as an initiative for lifting poor organic farmers by providing higher price, credit and improved community life. It is also a market for high value products in the global trade policies. Fair Trade Alliance Kerala (FTAK) is a small farmers’ organisation to access global market on fair trade in an equitable trading terms and improved income. The system provides better price to products compared to open market and benefited fair trade exporting. This paper by studying FTAK focused the impacts of it on income and highlights the increased production of organic crops, better prices, premium and schemes to farmers. The study revealed that fair trade farmers earned higher price (20 to 50 percent) for commodities and marketing of products to foreign countries without intermediaries and organic farming is a better option for increasing farmer’s income in India.Bangladesh J. Agril. Res. 44(3): 401-408, September 2019